Effectiveness of a family-centered psychological intervention program based on spiritual therapy and cognitive behavioral therapy on the lifestyle of patients with type 2 diabetes - Delara Sadat Madahzad; Reza Pourhosein; Masoud Gholamali Lavasani; Gholamali Afrooz (Social Determinants of Health)
Background: The aim of the present study was to design and validate a family-centered psychological intervention program based on spiritual therapy and cognitive behavioral therapy and its effectiveness on the lifestyle of patients with type 2 diabetes.